A Pre-Registered Test of a Correlational Micro-PK Effect: Efforts to Learn from a Failure to Replicate - Maier, Markus; Dechamps, Moritz (Journal of scientific exploration, 2022)
Micro-psychokinesis (micro-PK) research studies the effects of observers’ conscious or unconscious intentions on random outcomes derived from true random sources such as quantum random number generators (QRNGs). The micro-PK study presented here was originally planned, preregistered, and conducted to exactly replicate a correlational finding between two within-subject experimental conditions found in an original micro-PK dataset (n = 12,254) using a QRNG. However, after data collection and analyses, a data error was detected in the original to-be-replicated dataset. A reanalysis of the original correlation effect after error correction revealed strong evidence for the absence of a correlation in the original data. This study’s primary goal was to test the existence of a correlational micro-PK effect in the present data as specified in the pre-registration. In addition to this replication attempt, the present study also can be considered an unsystematic case report or field study on experimenter psi (e-psi), since a strong expectation was formed initially about the occurrence of an effect that indeed was objectively absent from the original data. This study’s results indicate no evidence for the existence of a correlational (and standard) micro-PK effect. In other words, the actual correlational data did not meet the experimenters’ conscious expectations, and thus no consciously based effect of e-psi on micro-PK was found. However, the change in evidence for the effect across time described by the sequential Bayes factor resembled a data pattern that also was frequently reported by the experimenters in past studies. Although these data did not meet the criterion of statistical significance, the marginal effects might be interpreted as weak influences based on unconscious e-psi. In addition, the trend observed matches both experimenters’ general beliefs about the occurrence of e-psi in micro-PK. These findings’ implications for the application of scientific methods to the study of micro-PK and psi in general are discussed.